Analysis and optimization experimental study on the influence of bolt end shape on eccentricity - Biao HOU; Wenjun JU; Zhen ZHANG; Xiaowei CHU; Kun PAN; Yinwei WANG; Hongzhi YANG (Meitan xuebao)
The bolt support is widely used in underground engineering construction due to its unique advantages. With the increase in engineering depth and the complex and variable geological conditions, higher requirements are being placed on the anchoring performance of bolts. The phenomenon of bolt eccentricity is common in rock and soil and underground support engineering, and it has a certain adverse effect on the working performance of the anchoring system. In this study, theoretical analysis, numerical simulation, and laboratory experiments were used to preliminarily investigate the influence mechanism of different end shapes of threaded steel bolts on the centering degree of the bolts. The aim was to clarify the impact characteristics of bolt eccentricity on anchoring performance and explore effective control strategies for bolt anchoring eccentricity based on independently designed bolts with different end shapes. The theoretical analysis revealed that the end shape of the bolt has a significant impact on its eccentricity. The conical tip of the bolt can easily penetrate the resin grout's sealing bag, reducing the resistance during the anchoring process when drilling and mixing the resin grout. Additionally, the protruding gear portion at the end can fix the position of the bolt relative to the borehole during the drilling and mixing process, thereby improving the eccentricity of the bolt. Numerical simulation analysis found that under smooth and rough borehole conditions, the bolts with gear-shaped and umbrella-shaped ends had motion trajectories closer to the center of the borehole compared to the prototype and conical-shaped bolts, resulting in an approximately 85% increase in centring rate. Experimental results showed that the eccentricity of the bolt during horizontal anchoring was higher than that during vertical anchoring. However, anchor bolts with gear-shaped and umbrella-shaped ends could restrict the motion trajectory of the bolt during the anchoring process, effectively preventing eccentricity. Moreover, these end shapes exhibited better eccentricity in the final anchoring state, with eccentricity approximately 81.9% and 86.7% higher than the prototype, and anchoring forces approximately 16.7% and 22.1% higher, respectively. The conical-shaped end resulted in a centring degree approximately 8.4% higher than the prototype and an anchoring force approximately 7.9% higher. The research results have certain theoretical and engineering application value for improving the centring effects and improving the anchoring performance.